Jessica Benjamin Discusses Her Work with Galit Atlas. Issue 6 (18th August 2022) - Benjamin, Jessica; Atlas, Galit
ABSTRACT: I'm honored to be here with Jessica Benjamin, one of the most sophisticated and profound thinkers in psychoanalysis. Jessica and I started working together nearly twenty years ago, right after I moved to New York. She was one of my first supervisors. Jessica taught me analytic freedom, analytic discipline and what brilliant thinking looks like. One might say that I grew up next to her, but in so many ways she raised me. Throughout the years our relationship developed to become a deep friendship and a professional collaboration. We wrote a paper together that was published at the IJP titled The Too Muchness of Excitement: Sexuality in Light of Excess, Attachment and Affect Regulation . Different versions of that paper are chapters in my first book " The Enigma of Desire " and in Jessica's last book " Beyond Doer and Done to ." Today I would like to talk with Jessica about her important contributions to psychoanalysis: her psychoanalytic work on intersubjectivity, early development and the mother infant-bond, her ideas of the Third, Doer and Done to and more. I would like to integrate the personal and the professional, theory and practice and look at the ways her feminist work, her philosophical thinking as well as her social activism are all organized around the theory of recognition.